PDTM-33. ATRX LOSS CONFERS ENHANCED SENSITIVITY TO COMBINED PARP INHIBITION AND RADIOTHERAPY IN PAEDIATRIC GLIOBLASTOMA MODELS. (5th November 2018) - Fazal Salom, Janat; Bjerke, Lynn; Carvalho, Diana; Boult, Jessica; Mackay, Alan; Pemberton, Helen; Molinari, Valeria; Clarke, Matthew; Vinci, Maria; Carceller, Fernando; Marshall, Lynley; Moore, Andrew; et al.
Abstract: Paediatric high grade glioma (pHGG) are defined by recurrent mutations in H3 histones, as well as frequent alterations in the SWI/SNF chromatin remodelling gene ATRX (α-thalassemia mental retardation X-linked), although the precise role of ATRX in tumorigenesis remains unclear. We sought to explore this using genomic analysis of patient samples, CRISPR-Cas9 engineered isogenic ATRX knockout (KO) cell lines and primary-patient-derived cultures. In combined retrospective and prospective cohorts of pHGG samples, we found ATRX mutations in 95/510 (18.6%) cases (27% hemispheric glioblastoma, 13% diffuse midline glioma), with the majority of truncating mutations found in the ADD domain, and missense mutations almost exclusively in the helicase domain. ATRX mutations commonly co-segregate with H3.3G34 and TP53 mutations, and define a subgroup of patients with a longer overall survival, though with a greater number of somatic mutations and copy number alterations than wild-type cases. CRISPR/Cas9-mediated ATRX KO targeting the ADD domain in TP53 mutant paediatric glioblastoma cells lead to loss of imprinting at the H19 locus in concert with upregulation of a pro-invasive transcriptional programme, though a slower rate of orthotopic tumour growth in vivo . ATRX deficient cells showed an abrogated DNA damage response, with prolonged accumulation of gH2AX foci after irradiation, and an increased dependency on PARP1 through persistent parylation and stalled replication forks. Screening ATRX-deficient isogenics and patient-derived cells against a library of >400 chemotherapeutics and small molecules identified a specific dependency for ATRX loss and sensitivity to distinct PARP inhibitor chemotypes, including catalytic inhibitors (olaparib, rucaparib), and PARP trappers (talazoparib). ATRX deficiency further conferred an enhanced radiosensitization of olaparib in vitro and a prolonged survival of mice treated with combined PARP inhibition and radiotherapy in vivo . These data suggest a synthetic lethality for PARP inhibitors in ATRX-deficient pHGG, and may represent a novel therapeutic strategy for these highly aggressive tumours.